Qualitative exploration of critical health literacy among Afghan and Congolese refugees resettled in the USA. (February 2019) - Im, Hyojin; Swan, Laura ET
Objectives: Previous research that revealed a high prevalence of low health literacy among immigrants and refugees tended to over emphasise functional health literacy as a risk factor for low health status and poor disease management. Despite a significant knowledge gap, little has been investigated regarding critical health literacy (CHL) in refugee populations whose culture deeply interweaves individual and contextual capacity to promote health. Design: This study adopted a qualitative approach to explore CHL that is built through community health workshops (CHWs) with Afghan and Congolese refugee communities in US resettlement. Setting: As part of a community-based participatory research project, the study was conducted with Afghan and Congolese refugees resettled in the USA. Method: A series of open-ended questions for focus group interviews were embedded in each workshop session explore health literacy skills and capacity over time. This study adopted a hybrid thematic design whereby the conceptual framework of CHL was applied to emergent themes from the data. Results: Thematic analysis revealed four major CHL thematic domains, as experienced and demonstrated by Afghan and Congolese refugee participants: (1) critical appraisal, (2) self-efficacy and confidence, (3) empowerment, and (4) collective problem solving. Conclusion: Study findings underline the importance of health education validating existing cultural knowledge and practices in a group setting so as to facilitate the building and enhancement of social support systems and community action for health promotion.